2020
DOI: 10.1177/2380084420962399
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 on Life Experiences of Essential Workers Attending a Dental Testing Facility

Abstract: COVID-19 poses a threat to health and well-being. Objectives: 1) To compare the impact of COVID-19 on the life experiences of essential workers attending a COVID-19 antibody testing clinic at a dental school. 2) To compare responses of dental, non–dental health care, and non–health care essential workers. 3) To assess acceptability/satisfaction of testing done in a dental setting. Method: A total of 984 participants completed a self-administered online questionnaire. Results: Over 90% were healthy (i.e., not i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 24 publications
0
8
0
1
Order By: Relevance
“…In maternity services, for example, healthcare staff need to adjust in changed practices that may be in direct conflict with evidence, professional recommendations or moral beliefs and values of HCWs [ 96 ]. Studies also show that surgeons [ 91 ], dental health staff [ 97 , 98 , 99 ] mental health staff and trainees [ 100 ], ophthalmologists [ 53 ], and community pharmacists [ 101 ] are exposed to increased emotional strain and vulnerable to mora l injury.…”
Section: Resultsmentioning
confidence: 99%
“…In maternity services, for example, healthcare staff need to adjust in changed practices that may be in direct conflict with evidence, professional recommendations or moral beliefs and values of HCWs [ 96 ]. Studies also show that surgeons [ 91 ], dental health staff [ 97 , 98 , 99 ] mental health staff and trainees [ 100 ], ophthalmologists [ 53 ], and community pharmacists [ 101 ] are exposed to increased emotional strain and vulnerable to mora l injury.…”
Section: Resultsmentioning
confidence: 99%
“…What is more, the positive ‘psychological effect’ of rapid COVID-19 testing in dental settings cannot be underestimated, enabling reassurance, and strengthening patients’/staff confidence [ 30 ]. As a result, this approach, although costly and logistically challenging in resource-limited areas, would improve the patient attendance rate and reduce the employee’s absence rate [ 30 ]. Most importantly, regular rapid LFATs are recommended as a routine protocol for staff members who provide special care dentistry for medically compromised individuals, persons with special needs (intellectual or developmental disabilities), and frail care home residents, to limit the treatment-related risk of SARS-CoV-2 infection [ 31 ].…”
Section: Optimizing Risk-reduction: Teleconsultations and Chair-side Tests Following Immunity Enhancementmentioning
confidence: 99%
“…However, the advantages of applying LFATs as an additional measure to protect DCWs while resuming the routine dental care prevail over their limitations (Table 1). What is more, the positive 'psychological effect' of rapid COVID-19 testing in dental settings cannot be underestimated, enabling reassurance, and strengthening patients'/staff confidence [30]. As a result, this approach, although costly and logistically challenging in resource-limited areas, would improve the patient attendance rate and reduce the em-ployee's absence rate [30].…”
Section: Rapid Antigen Tests: a Gamechanger?mentioning
confidence: 99%
“…Fontana et al found that DHCWs were vulnerable to the threat of COVID-19 and its psychological impact to the same extent as other essential workers. 5 The dental profession is considered high-risk due to contact with the potentially contaminated saliva or blood carrying diverse pathogens, such as the hepatitis B virus (HBV), the hepatitis C virus (HCV) and the human immunodeficiency virus (HIV) responsible for acquired immunodeficiency syndrome (AIDS), as a result of occupational accidents. 6 Contagion with SARS-CoV-2 through direct contact with the infected patient while performing dental procedures is possible.…”
Section: Introductionmentioning
confidence: 99%